The efficacy of the legal framework regulating PPE pollution arising from COVID-19 in South Africa, and proposed reforms - Murcott, Melanie (University of Pretoria, 2023)
Mini Dissertation (LLM (Multidisciplinary Human Rights))--University of Pretoria, 2022.